Synthesis of furo[2,3-b]pyran-2-ones through Ag(I)- or Ag(I)-Au(I)-catalyzed cascade annulation of alkynols and alpha-ketoesters - Thorat, Sagar S.; Kataria, Priyanka; Kontham, Ravindar (Organic Letters, 2018)
Ag(I)- or Ag(I)-Au(I)-catalyzed cascade annulation of alkynols (5-hexyn-1-ol systems) with a-ketoesters involving a dual activation process (pi and sigma) has been developed for the first time. This reaction proceeds through cycloisomerization of alkynol to give the 6-endo-enol ether followed by annulation with an alpha-ketoester to furnish furo[2,3-b]pyran-2-ones in good yields. Chemical structures of all products were rigorously confirmed by single crystal X-ray analysis and analogy.